2020
DOI: 10.36076/ppj.2020/23/e297
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Opioid Prescribing and Drug Enforcement Agency (DEA) Action Against Physicians: An Analysis of DEA Database 2004-2017

Abstract: Background: Prescribing opioids has become a challenge. The US Drug Enforcement Agency (DEA) and Centers for Disease Control and Prevention (CDC) have become more involved, culminating in the March 2016 release of the CDC’s “Guidelines for Prescribing Opioids for Chronic Pain.” Objectives: Given the new guidelines, we wanted to see if there have been any changes in the numbers, demographics, physician risk factors, charges, and sanctions involving the DEA against physicians who prescribe opioids, when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Finally, drug trafficking was the most convicted crime (accounting for 54.2% of all convicted cases), followed by fraud (19.1%), money laundering (11.0%), and manslaughter (5.6%) [2]. Kim and Sibai (2020) have reported that the overall risk of DEA action as a percentage of total physicians is small but not insignificant; however, the overall rates of DEA prosecution have increased. Also, new risk factors include the type of degree of the physician (osteopath versus allopath) and being in private practice, with a subtle trend toward foreign graduates being at higher risk [11] .Finally, they proclaim that more subtle charges have been added involving interpretation of the medical purpose of opioids and standard of care for their use [11].…”
Section: Opioids and Medical Malpracticementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, drug trafficking was the most convicted crime (accounting for 54.2% of all convicted cases), followed by fraud (19.1%), money laundering (11.0%), and manslaughter (5.6%) [2]. Kim and Sibai (2020) have reported that the overall risk of DEA action as a percentage of total physicians is small but not insignificant; however, the overall rates of DEA prosecution have increased. Also, new risk factors include the type of degree of the physician (osteopath versus allopath) and being in private practice, with a subtle trend toward foreign graduates being at higher risk [11] .Finally, they proclaim that more subtle charges have been added involving interpretation of the medical purpose of opioids and standard of care for their use [11].…”
Section: Opioids and Medical Malpracticementioning
confidence: 99%
“…Kim and Sibai (2020) have reported that the overall risk of DEA action as a percentage of total physicians is small but not insignificant; however, the overall rates of DEA prosecution have increased. Also, new risk factors include the type of degree of the physician (osteopath versus allopath) and being in private practice, with a subtle trend toward foreign graduates being at higher risk [11] .Finally, they proclaim that more subtle charges have been added involving interpretation of the medical purpose of opioids and standard of care for their use [11]. It is an understandable inference that as the need for midlevel providers intensifies and their resulting responsibilities increases that opioid prescribing litigation and malpractice claims will a for gone conclusion.…”
Section: Opioids and Medical Malpracticementioning
confidence: 99%
“…Also, new risk factors include the type of degree of the physician (osteopath versus allopath) and being in private practice, with a subtle trend toward foreign graduates being at higher risk. 29 Finally, they proclaim that more subtle charges have been added involving interpretation of the medical purpose of opioids and standard of care for their use. 29 Mitigating Opioid-Prescribing Risk Thorough and diligent documentation and opioid monitoring by the opioid prescriber are the most effective foundations for building a defense in an opioid medical malpractice case.…”
Section: Opioids and Medical Malpracticementioning
confidence: 99%
“…Another difficulty is accounting for how PDMP functions and legislation constantly change, potentially impacting the applicability of prior PDMP research. PDMP regulations may also be implemented at the same time as other opioid misuse mitigation efforts, such as greater law enforcement efforts; the existence of multiple independent variables confounds findings [28][29][30][31][32]. There have also been consequential initiatives at the professional level that likely confound research findings, such as the 2016 publication of the CDC's Guidelines for Prescribing Opioids for Chronic Pain [33].…”
Section: Introductionmentioning
confidence: 99%